IMPLEMENTASI SISTEM PAKAR DIAGNOSA PENYAKIT PADA SAPI MENGGUNAKAN METODE VARIABLE CENTERED INTELLIGENT RULE SYSTEM (VCIRS) BERBASIS WEBSITE STUDI KASUS PETERNAK BERKAH FARM - Luthfi Nur Haikal; Dimas Abisono Punkastyo (Journal of Research and Publication Innovation, 2025)
This study aims to develop an intelligent expert system for diagnosing cattle diseases using the Variable Centered Intelligent Rule System (VCIRS) method. The system was designed to assist breeders and livestock extension officers in identifying early symptoms of major diseases that commonly affect cattle, such as Foot and Mouth Disease (FMD), Mastitis, Anthrax, Parasite Infection, and Brucellosis. The system applies VCIRS as the reasoning engine, which analyzes the correlation between symptoms and diseases based on a rule-based approach and the variable certainty of each symptom. The implementation is web-based, developed using the PHP programming language and MySQL database, making it easily accessible to users. The system determines the diagnosis by matching at least four of five disease indicators and produces detailed recommendations for prevention and treatment. Testing results show that the system achieves high accuracy and efficiency in providing diagnostic conclusions. This research contributes to the field of artificial intelligence applications in animal health management, enabling faster disease identification, supporting decision-making for farmers, and minimizing livestock mortality rates caused by infectious diseases.